The Barriers and Problems of ISO Implementation in Iranian Manufacturing Companies - Seyed Faramarz Ghoreni (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2010)
At the present time, suitable and on time response to customers need’s is the most important factor for success, and many organizations focus on quality according to ISO standards. This quantitative - descriptive study, was conducted related to the barriers and problems of ISO implementation in manufacturing companies, reviewing the critics and supports toward the ISO all over the world and then investigates the reason for mal implementation in manufacturing companies of the country. Research data were gathered through al 9 item questionnaire regarding the implementation of ISO standards (ISO 9000:2000) in lickerts format. The society of study includes all companies intending to achieve ISO 9000:2000 supervised by the ministry of industry in Tehran province. It was requested that, three middle level managers answer the questions. After two months, 54 companies completed the questionnaires. Results showed that the implementation of ISO management system in every organization’s needs are foundation procedure and also top level managers and authorities should accept such process in their organizational management practice. Such evidence was not observed in this study and in contrast there was a little trend in this field which did not motivate the managers to provide the needed infrastructure for documentation, data transfer and contribution with other management levels. It seems that top level managers of Iranian Industrial companies do not pay significant attention to such important problem and it will be followed by many negative consequences for local manufacturing centers in their future competition in the world economy.